Nacjonalizm walijski - Wojtashak, Andrew (Lviv Politechnic Publіshing House, 2016)
Prezentowany artykuł dotyczy Walijczyków, jednego z narodów zamieszkujących obszar Wielkiej Brytanii. Celem przeprowadzonych badań jest pokazanie specyfiki walijskiego nacjonalizmu, który pomimo silnej angielskiej dominacji, pozwolił tej nacji na wielowiekowe przetrwanie, tradycji, kultury, języka oraz stworzenia racjonalnych prób utrzymania własnej odrębności na Wyspach Brytyjskich. Analiza brytyjskich nacjonalizmów pokazuje, że Walijczycy są najczęściej traktowani jako “ostatni w kolejce”, po Anglikach, Irlandczykach z Północy i Szkotach. Walijczycy prowadzą działania w obronie własnej kultury i języka, stopniowo dąćąc do stworzenia czytelnej odrębności. Pytanie, które się pojawia sprowadza się do stwierdzenia, czy istnieją granice poza które takie ewolucyjne (dewolucyjne) zmiany ze strony Walijczyków nie powinny wykraczać? Jest to proces, który trwa. Początek w przypadku Walii dała Plaid Cymru. Dziś jest to narodowa sprawa całej Cymru. Być może, wspieranie działań pozwalających na odczucie takiej odrębności, pozwoli na uregulowanie ralacji w sposób oczekiwny przez Walijczyków. Rodzą się jednak nowe pytanie, mogące być przedmiotem dalszych badań: czy następnym krokiem nie będą działania separatystyczne? I wreszcie pytanie: czy we współczesnej nam rzeczywistości nie będziemy mieli do czynienia ze wzrostem separatyzmów, również wśród średnich i małych narodów? Kwestie t te powinny być przedmiotem stałej anlizy, która umożliwiałaby poszukiwanie rozwiązań problemów w sposób bezkonfliktowy. The article refers to the Welsh, one of nations inhabiting the area of the United Kingdom. The aim of the study is to demonstrate the specificity of Welsh nationalism, which despite strong English domination, allowed this nation to preserve its tradition, culture, language for centuries, and create a rational attempt to maintain their own identity on the British Isles. Analysis of British nationalism shows that the Welsh are most often treated as the “last in line” after Englishmen, Irishmen from North and Scots. In the modern formula of nationalism, it is not a phenomenon but rather rebirth and compilation of existing views, born in different environments of the local, regional or even national. People are united through language, politics, economics, tradition or religion. Taking into account processes in society, the Welsh are associated with the development of the centuries-old tradition, distinct awareness, equally important with the possibility of displaying, which is evident in activity of Plaid Cymru (Welsh National Party). Welsh activities are carried out in defense of their own culture and language, gradually seeking to create a clear distinction. The question that arises is reduced to determining whether there are limits beyond which such evolutionary (devolutionary) changes from the Welsh should not go? It is lasting process. The case of Wales gave Plaid Cymru. Today it is a national issue across Cymru. Changes in attitudes of peoples inhabiting the area of the United Kingdom, efforts to confirm their own identity are implemented in different ways. Scottish separatism attempts to create an independent state. Despite the existence of compromise between Belfast and London on wide degree of autonomy by the Irish of Ulster separatist aspirations can return at any time. It is difficult today to think about total independence of Wales. Nevertheless, the Cymru community shows that the identified national goals, providing universal agreement on reforming the United Kingdom. Perhaps, supporting measures to make sense of such a separation will regulate relations expected by Welsh. They raise, however, a new question, which may be the subject of further research: whether will separatist activities not be the next step? And the final question is whether in our contemporary reality, we will not have to deal with the increase in separatism among medium and small nations as well. These problems should be the subject of constituent analysis which would enable search for solutions in a non-confrontational manner.
Welsh nationalism
Keywords: nacjonalizm; Walia; Plaid Cymru; język; kultura; tradycja; autonomia; nationalism; Wales; Plaid Cymru; language; culture; tradition; autonomy